Energy Consumption and Financial Development in Sub-Saharan Africa: A Panel Econometric Analysis (2013)
This paper investigated the energy consumption-financial development linkage for Sub-Saharan Africa (SSA). Annual data for 26 countries spanning the period 1996 to 2009 was used to elicit answers on the questions of interest. This is the first attempt, as far as we are aware, at examining the linkage between shocks to and response of the energy and financial markets of SSA economies. Recent panel causality techniques are deployed to probe causal orderings both in the short- and long-run. The results suggest that regardless of the financial development measure, there is weak evidence for short-run causality. Contrariwise, there appears to be ample evidence in support of long-run causality particularly flowing from private sector credit as a share of GDP to total energy consumption. For electricity consumption, there is short-run and long-run causality from private sector credit to GDP ratio. In sum, these plausibly imply that a deeper financial system effectively allocates resources to the private sector enabling a scaling up in operations and by extension higher energy requirements.